Mercury concentrations in wild humpback whales (Megaptera novaeangliae) sampled in the Colombian Pacific and in Antarctic Peninsula (2017)
"The G stock of Humpback whales (Megaptera novaeangliae) conducts one of the longest cetacean migration from Antarctic Peninsula (feeding area) to the Southeast Pacific (breeding and calving area), being exposed to several pollutants such as mercury, which has been previously reported in the Antarctic. In order to assess the mercury concentration in skin and blubber of Humpback whales from the G stock, samples were collected in the Antarctic Peninsula (2015, n=15) and in the Colombian Pacific (Choco Province) (2015, n=14; 2016, n=42). Total mercury concentrations ([THg]) were measured by atomic absorption spectrometry (AMA-454, Altec). Results revealed significant differences in [THg] by tissue type in the same individual (n=22; p<0.05)..."